An Effective Technique For Generation And detection Of QR code (International Journal of Advanced Research in Computer Science, 2017)
This paper focuses on the concept of QR code ie. Quick Response Code. It is used instead of bar code because it has more data holdingcapacity than bar code with high speed of detection and accuracy. Quick Response (QR) code has been widely used in the automatic identificationfields. In order to adapting the various sizes, a little dirty or damaged, and various lighting condition of bar code image, this proposes a novelimplementation of real time Quick Response code recognition which is an efficient technology used for data transferring.QR code is 2D code which read data horizontally and vertically; stores alphanumeric characters. In order to adapting various sizes, various graylevel values, and under various lighting conditions of real bar code image, a high speed, high accuracy. Mobile phones can be secure with generationand detection of QR code.Keywords: QR code, generation, detection, encryption.